Effect of multi-step annealing with different heating rates on magnetic properties of Fe-Si-B-P-Cu nano-crystalline alloy - Ziyan Hao; Linzhuo Wei; Yuanfei Cai; Yaocen Wang; Mingliang Xiang; Fang Zhao; Yan Zhang; Nikolai S Perov; Chongde Cao (Materials Research Express, 2022)
The crystallization behaviors of Fe _83 Si _4 B _8 P _4.3 Cu _0.7 amorphous alloy with different heating rates and magnetic softness of annealed alloys have been widely studied. The rapid heating significantly helped with the decrease of coercivity for annealed samples compared with that for slow heating. It is found that the peak temperature ( T _p1 ) of the first crystallization stage in DSC curves is a critical temperature parameter to distinguish the nucleation and growth processes of α -Fe phase. When the temperature at a constant heating rate is beyond the T _p1 , the nucleation process should be almost finished. The necessary temperature range of high heating rate (400 K min ^−1 ) for the improvement of magnetic softness has been determined from 650 K to 740 K through multi-step annealing with different heating rates. The shortened temperature window of rapid heating and partial rapid heating may simplify and improve the annealing process of high-performance soft magnetic materials in industry. The multi-step annealing with various heating rates also provides a promising strategy for the investigation of crystallization behaviors of amorphous alloys.